A Longitudinal Study of E-Cigarette, Cigarette, and Marijuana Use Sequence in Youth - Erika Westling; Julie C. Rusby; Ryann Crowley; John M. Light (SAGE Publishing, 2022)
Objective There is evidence linking youth use of electronic (e-) cigarettes to subsequent cigarette and marijuana use, raising public health concerns. We examined the sequence of use of e-cigarettes, conventional cigarettes, and marijuana in a longitudinal sample of adolescents, to determine if use of e-cigarettes often preceded use of other substances. Methods We collected self-reports from 1123 Oregon adolescents (52% female; 37% Hispanic) longitudinally from 8 th to 11 th grade (8 total surveys) regarding their lifetime (ever use) and current use (last 30 days) of e-cigarettes, cigarettes, and marijuana. If applicable, students also reported the delivery method of their current marijuana use. Results Almost 10% of adolescents reported using e-cigarettes prior to use of cigarettes or marijuana, and the majority of these youth initiated use of marijuana, cigarettes, or both by 11 th grade. More youth transitioned from e-cigarette use to marijuana use then from e-cigarettes to use of conventional cigarettes. Participants who were co-using e-cigarettes and marijuana in 11 th grade had an increased likelihood of consuming marijuana via vaping, dabbing, and edibles, compared to those who were only using marijuana. Discussion E-cigarettes were often the first substance used in this longitudinal sample, and more of these youth subsequently used marijuana compared to cigarettes. While research has focused on the progression from e-cigarettes to cigarettes in youth, these findings indicate that more attention should be focused on the subsequent initiation of marijuana.